Townspeople, Group Belonging, and Collective Agency in Post-Carolingian Historiography - Wassenaar, Jelle (The Past Through Narratology: New Approaches to Late Antiquity and the Early Middle Ages, 2022)
This article deals with depictions of townspeople in tenth- and early eleventh-century narratives. It argues that during the tenth century the narrative function of these groups in historiography changed fundamentally. In Carolingian and earlier tenth-century narratives, townspeople tend to play largely tangential and passive roles; from around the middle of the tenth century, authors began to increasingly accord agency and a more central role to townspeople. Although these mentions of townspeople in post-Carolingian histories have traditionally been approached as providing a window into processes of ‘embryonic’ urbanisation, this paper suggests that the shift in their narrative function must also be understood in the context of the changing nature of diocesan identity politics created through the dissolution of the Carolingian Empire.<br